Teachers Preparedness on Implementation of Merit Selection Plan: Basis for Professional Development Program Educators - Camo, Jenel; Uy, Devina; Molina, Jonathan (Yayasan Nurul Yakin Bunga Tanjung, 2024)
The study described teachers’ demographic profile and preparedness for the Merit Selection Plan. It also determined if differences exist among their demographic profile. This employed quantitative research design with 44 elementary teachers from eight schools in the Cagayancillo District, Palawan, Philippines. The research utilizes frequency and percentage to describe the teachers’ profile and weighted mean for their preparedness. Independent t-tests and a series of one-way ANOVA were used to determine the differences in the teachers’ preparedness for the Merit Selection Plan based on their profiles. Notably, respondents consider physical and financial challenges in their preparedness. They exhibit high readiness for career advancement, engage in frequent classroom observations, and adeptly integrate learnings from training and seminars to enhance productivity. However, the study reveals no significant difference in the teachers’ preparedness for the Merit Selection Plan considering their profile. This finding will inform decision-making processes and contribute to the ongoing discourse on teacher preparedness and professional development.